Anti-Mycobacterial Evaluation of 7-Chloro-4-Aminoquinolines and Hologram Quantitative Structure-Activity Relationship (HQSAR) Modeling of Amino-Imino Tautomers - Marcelle L. F. Bispo; Camilo H. S. Lima; Laura N. F. Cardoso; André L. P. Candéa; Flávio A. F. M. Bezerra; Maria C. S. Lourenço; Maria G. M. O. Henriques; Ricardo B. Alencastro; Carlos R. Kaiser; Marcus V. N. Souza; Magaly G. Albuquerque (MDPI AG, 2017)
In an ongoing research program for the development of new anti-tuberculosis drugs, we synthesized three series (A, B, and C) of 7-chloro-4-aminoquinolines, which were evaluated in vitro against Mycobacterium tuberculosis (MTB). Now, we report the anti-MTB and cytotoxicity evaluations of a new series, D (D01-D21). Considering the active compounds of series A (A01-A13), B (B01-B13), C (C01-C07), and D (D01-D09), we compose a data set of 42 compounds and carried out hologram quantitative structure-activity relationship (HQSAR) analysis. The amino-imino tautomerism of the 4-aminoquinoline moiety was considered using both amino (I) and imino (II) forms as independent datasets. The best HQSAR model from each dataset was internally validated and both models showed significant statistical indexes. Tautomer I model: leave-one-out (LOO) cross-validated correlation coefficient (q2) = 0.80, squared correlation coefficient (r2) = 0.97, standard error (SE) = 0.12, cross-validated standard error (SEcv) = 0.32. Tautomer II model: q2 = 0.77, r2 = 0.98, SE = 0.10, SEcv = 0.35. Both models were externally validated by predicting the activity values of the corresponding test set, and the tautomer II model, which showed the best external prediction performance, was used to predict the biological activity responses of the compounds that were not evaluated in the anti-MTB trials due to poor solubility, pointing out D21 for further solubility studies to attempt to determine its actual biological activity.